Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006460
|View full text |Cite
|
Sign up to set email alerts
|

Conventional occlusion versus pharmacologic penalization for amblyopia

Abstract: Differences between protocol and review The new risk of bias table introduced by the Cochrane Collaboration was used to assess methodological quality of included studies. Post peer review for the manuscript, a decision was made to exclude systemic therapy and therefore the search strategies were amended accordingly and the review process started again with the new search results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…A Cochrane systematic review concluded that atropine was as effective as patching and that compliance with atropine was better. 40 Traditional treatment protocols involved daily application of 1% atropine, 41 but for moderate amblyopia (Snellen 6/24 or better) application only at weekends has been shown to be as effective. 42 Weekend-only atropine reduces potential systemic side effects such as flushing and tachycardia, which occur in about 5% of children with a daily regimen.…”
Section: Atropinementioning
confidence: 99%
“…A Cochrane systematic review concluded that atropine was as effective as patching and that compliance with atropine was better. 40 Traditional treatment protocols involved daily application of 1% atropine, 41 but for moderate amblyopia (Snellen 6/24 or better) application only at weekends has been shown to be as effective. 42 Weekend-only atropine reduces potential systemic side effects such as flushing and tachycardia, which occur in about 5% of children with a daily regimen.…”
Section: Atropinementioning
confidence: 99%
“…Recent studies have pointed to the efficacy of atropine penalization in the treatment of moderate degrees of amblyopia. 16,17 Cycloplegic retinoscopy can determine the refractive status of the graft as sutures are removed. Refractive correction is usually given once all sutures are removed but an ''interim'' correction may be needed to facilitate amblyopia therapy in cases of anisometropia and profound amblyopia.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…In this review we considered only strabismic amblyopia; interventions for other types of amblyopia have been evaluated in a series of Cochrane reviews (Antonio-Santos 2014; Li 2009; Shotton 2012). …”
Section: Introductionmentioning
confidence: 99%